Easy Rider og drømmen om frihed - Peters, Rikke Louise (Slagmark - Tidsskrift for idéhistorie, 2018)
Peters Fondas road movie Easy Rider forms the spine in this essay, which hunts the idea of freedom on the road. The essay first takes a closer look at Easy Rider and the ideals the creators of the film wanted to describe. Then moves on to take a closer look at later political receptions of the film and finally takes a closer look at the ideals that bring young women to chase freedom on the roads.